Strategic Integration Of The Cambridge Curriculum For Character Building In Islamic Education: A Qualitative Case Study - Lilik Prasetyarini; Mudofir Mudofir; Fitri Wulandari; Jumintono Jumintono (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the strategy of integrating the Cambridge Curriculum into character building within Islamic education, with a case study at Madrasah Mu’allimin Muhammadiyah Yogyakarta. The study is motivated by the urgent need for an educational model that balances academic excellence with strong moral formation, especially amid increasing cases of juvenile delinquency in Indonesia. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings show that curriculum integration is carried out systematically through three stages: planning, implementation, and evaluation. Planning includes vision alignment, curriculum mapping, and teacher capacity building; implementation integrates Cambridge subjects with Islamic values across intracurricular, co-curricular, and boarding programs; and evaluation applies multi-layered monitoring at both unit and foundation levels, combining academic outcomes with behavioral evidence. This model creates a holistic learning ecosystem that enhances academic performance while fostering discipline, responsibility, reflective thinking, social awareness, and leadership skills. Theoretically, the study contributes to the literature on curriculum adaptation and character education, while practically offering a transferable framework for policymakers and Islamic institutions to contextualize global curricula without compromising their local identity.